Vasodilators and low-dose acetylsalicylic acid are associated with a lower incidence of distinct primary myocardial disease manifestations in systemic sclerosis: results of the DeSScipher inception cohort study. Issue 11 (7th August 2019) - Valentini, Gabriele; Huscher, Dörte; Riccardi, Antonella; Fasano, Serena; Irace, Rosaria; Messiniti, Valentina; Matucci-Cerinic, Marco; Guiducci, Serena; Distler, Oliver; Maurer, Britta; Avouac, Jérôme; Tarner, Ingo H; et al.
Abstract : Objectives: To investigate the influence of vasodilator drugs on the occurrence of features depending on myocardial ischaemia/fibrosis (ventricular arrhythmias, Q waves, cardiac blocks, pacemaker implantation, left ventricular ejection fraction (LVEF) <55%, and/or congestive heart failure and sudden cardiac death) in systemic sclerosis (SSc). Methods: 601 patients with SSc were enrolled from 1 December 2012 to 30 November 2015 and had a second visit 0.5–4 years apart. 153 received no vasodilators; 448 received vasodilator therapy (ie, calcium channel blockers and/or ACE inhibitors or angiotensin II receptor blockers or combinations of them), 89 of them being also treated with either endothelin receptor antagonists or PDE5 inhibitors or prostanoids. Associations between the occurrence of myocardial disease manifestations and any demographic, disease and therapeutic aspect were investigated by Cox regression analysis. A Cox frailty survival model with centre of enrolment as random effect was performed. Results: During 914 follow-up patient-years, 12 ventricular arrhythmias, 5 Q waves, 40 cardiac blocks, 6 pacemaker implantations and 19 reduced LVEF and/or congestive heart failure (CHF) occurred. In multivariate Cox regression analysis, vasodilator therapy was associated with a lower incidence of ventricular arrhythmias (p=0.03); low-dose acetylsalicylic acid (ASA) with a lower incidence of cardiac blocks and/or Q waves and/or pacemaker implantation (p=0.02); active disease with a higher incidence of LVEF <55% and/or CHF and cardiac blocks and/or Q waves and/or pacemaker implantation (p=0.05). Conclusions: The present study might suggest a preventative effect on the occurrence of distinct myocardial manifestations by vasodilator therapy and low-dose ASA.